Using Spiritual Intelligence to Transform Organizational Cultures - McGhee, P; Grant, P (Business and Organization Ethics Network (BON), 2017)
Recently spirituality has become a viable topic of discussion for management scholars seeking a means to enhance work cultures and improve organisational effectiveness. However, the path from spirituality to transforming organisational culture is not immediately obvious. Fortunately, several authors have developed frameworks that provide connections. In particular, the notion of spiritual intelligence (SI hereafter) is helpful. This paper begins by describing spirituality and SI in the context of organisational transformation. It then details research involving working professionals that sought to answer the question: “How (and why) might SI transform organisational culture to be more ethical?” It concludes with discussion and implications of developing and practicing SI in organisational contexts.